Ekonomi Yang Inklusif Dan Berkelanjutan: Analisis Keuangan Daerah, Kemiskinan, Dan Teknologi Untuk Mewujudkan SDGS 2030 - Herman, Nur Ashilah Raihanah; Muchtar, Masruri; Sihombing, Pardomuan Robinson (Universitas Cenderawasih, 2024)
Sustainable Development Goals (SDGs) emerge as a universal commitment to address social issues, prioritize inclusive economic growth, and reduce inequality. Local governments become the main pillar in achieving the 2030 SDGs, alongside other factors such as GDP per capita and economic inclusivity by emphasizing regional equity and enhancing local self-reliance. This research analyzes the impact of regional finances, poverty, and technology on economic growth to achieve an inclusive and sustainable economy. The data is sourced from the Central Bureau of Statistics and the Directorate General of Fiscal Balance for the years 2020-2022, covering all provinces in Indonesia. Using panel data regression (fixed effect model), the test results find that local revenue, revenue-sharing funds, and technology positively impact per capita economic growth, while poverty shows a negative influence. The implications of these findings highlight the need for a comprehensive study related to the implementation of fiscal decentralization and technology investment to achieve the 8th goal of the 2030 SDGs.